FACILITATION OF NEUROFUNCTIONAL TRAINING WITH TDCS AND RTMS ON THE LEFT DORSOLATERAL PREFRONTAL CORTEX IN CHILDREN WITH AUTISM SPECTRUM DISORDER: A RANDOMIZED, PLACEBO-CONTROLLED, DOUBLE-BLIND CLINICAL TRIAL (CIPEEX, 2025)
The objective of this study is to compare the effects of ten sessions of neurofunctional training associated with anodal transcranial direct current stimulation (tDCS) or high-frequency repetitive transcranial magnetic stimulation (rTMS) on the left dorsolateral prefrontal cortex in the domain of Participation of the International Classification of Functioning, Disability and Health (ICF) in children with Autism Spectrum Disorder (ASD).in children with Autism Spectrum Disorder (ASD).  This is a randomized, placebo-controlled, double-blind clinical trial involving 48 children diagnosed with ASD. The children will be randomly assigned to four groups: tDCS experimental group: neurofunctional training associated with active tDCS; tDCS control group: neurofunctional training associated with placebo tDCS; rTMS experimental group: neurofunctional training performed after active rTMS; and rTMS control group: neurofunctional training performed after placebo rTMS. Participants will be assessed one week before the intervention, one week and one month after the end of the interventions, using the Childhood Autism Rating Scale, Pediatric Assessment of Dysfunction Inventory, and Participation and Environment Measure - Children and Youth. The interventions will consist of five sessions per week, carried out over two consecutive weeks. Neurofunctional training will consist of a circuit of activities (10 minutes) and treadmill training (10 minutes). Neurofunctional training and tDCS application will be performed synchronously for 20 minutes. rTMS will be performed for 20 minutes, with the participant at rest and after the participants have completed the neurofunctional training.
Keywords: autism spectrum disorder; child; participation; transcranial magnetic stimulation; and transcranial direct current stimulation